2011
DOI: 10.1111/j.1365-294x.2011.05233.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of living in closed societies: lessons from a long‐term socio‐genetic study on Bechstein’s bats

Abstract: Understanding the ecological, behavioural and genetic factors influencing animal social systems is crucial to investigating the evolution of sociality. Despite the recent advances in population genetic methods and the analysis of social interactions, long-term studies exploring the causes and consequences of social systems in wild mammals are rare. Here, we provide a synthesis of 15 years of data on the Bechstein's bat (Myotis bechsteinii), a species that raises its young in closed societies of 10-45 females l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 89 publications
(219 reference statements)
0
75
0
4
Order By: Relevance
“…Daubenton's bats live in ‘fusion-fission colonies’, in which the bats in the same roosting refuge form a ‘loose colony’ (40). The ‘fused colony’ is built by several subgroups, while fission occurs at the time of roost switching by subgroups breaking apart and mixing, ending up in various new roosts (41). This strategy has several ecological advantages, but unfortunately it also facilitates the efficient spreading of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Daubenton's bats live in ‘fusion-fission colonies’, in which the bats in the same roosting refuge form a ‘loose colony’ (40). The ‘fused colony’ is built by several subgroups, while fission occurs at the time of roost switching by subgroups breaking apart and mixing, ending up in various new roosts (41). This strategy has several ecological advantages, but unfortunately it also facilitates the efficient spreading of infections.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, unlike most other mammalian systems (Schalk and Forbes 1997; Zuk and McKean 1996), females of most temperate zone bats have higher levels of parasite infection than males (e.g., Reckardt and Kerth 2009). Contact between the philopatric, closed female maternity colonies, and between females and males, is very rare during summer (Burland and Wilmer 2001; Kerth and van Schaik 2012). This results in limited horizontal transmission (used here as parasite exchange between different host colonies) opportunities for contact-transmitted parasites during this time (Bruyndonckx et al 2009b; van Schaik et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mite infection increases host grooming activity and metabolism (Giorgi et al 2001), and thus may impose a substantial cost, especially to juvenile hosts in maternity colonies (Lourenço and Palmeirim 2007). A study of mite population genetic structure across maternity colonies in M. myotis and Myotis bechsteinii , the latter having a similar social organization as M. nattereri (Kerth and van Schaik 2012; Rivers et al 2005), found contrasting levels of genetic diversity and genetic differentiation between the maternity colonies of the two host species (van Schaik et al 2014). Nevertheless, in both M. myotis and M. bechsteinii , substantial horizontal transmission of mites during the autumn mating season was implicated but could not be examined.…”
Section: Introductionmentioning
confidence: 99%
“…M. bechsteinii were wild caught in a forest near the city of W€ urzburg, Germany (latitude: N49 43 0 , longitude: E9 49 0 ), where the species has been studied for more than two decades (Kerth & van Schaik 2012). A 3 mm diameter wing biopsy was taken and stored in silica beads prior to DNA extraction.…”
mentioning
confidence: 99%
“…In this study, we sequenced, assembled, and phylogenetically validated the mitogenome of M. bechsteinii, a species whose population genetic structure and social behaviour has been intensively studied (Kerth & van Schaik 2012). This mitogenome is a resource for phylogenetic, biomedical, and on-going conservation studies.…”
mentioning
confidence: 99%